Population dynamics of anchovy pekto (Stolephorus waitei) in the waters of Malacca Strait, North Sumatra, Indonesia - Miswar Budi Mulya; ARLEN HANEL JHON; ZULHAM APANDY HARAHAP (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Mulya MB, Jhon AH, Harahap ZA. 2021. Population dynamics of anchovy pekto (Stolephorus waitei) in the waters of Malacca Strait, North Sumatra, Indonesia. Biodiversitas 22: 2693-2698. Anchovy pekto or Stolephorus waitei (Engraluidae: Clupeiformes) is one of the fish in the eastern coastal part of North Sumatra, occupying the waters of Malacca Strait. This research presents the population dynamics of S. waitei following its age, growth, mortality, and recruitment pattern based on the length-frequency data. Fork length (FL) and total weight (TW) data of S. waitei were collected at three sites from April to September 2018. A total of 1994 specimens with FL from 4.0 to 6.7 cm and TW from 0.2 to 2.3 g with the length-weight relationship of TW = 0.073FL3.0046 (R2=0.765) indicated a near isometric and positive allometric growth in the water region. The relative condition factor (Kn) ranged from 1.01 to 1.02, indicating an estimate of good condition of the fishes. The growth parameters based on von Bertalanffy was 6.56 cm (L?) with the growth coefficient (K) of 0.34 yr-1 and t0 (anchovy age at zero length ) of 0.6506. The total mortality (Z), natural mortality (F), and catch mortality (M) of S. waitei were 0.64, 1.39, and 0.75 yr-1 respectively, which suggest that the fishing activities of S. waitei are still in normal intensity. The recruitment pattern of S. waitei was stable between April and August with its peak in June by 14.21%. The fishing activities may then be limited during the spawning months (May to June) of S. waitei to maintain their population in the Strait of Malacca.